Tarekat dalam Islam : spiritualitas masyarakat modern - Kahmad, Dadang, 1952- (Bandung : CV Pustaka Setia, 2002)
Practice of Islamic spiritualism in modern society in Indonesia
Revision of the author's thesis (doctoral)--Universitas Padjadjaran, 1999
Daftar pustaka : p. 193-204
Keywords: Islam -- Indonesia; Sufism -- Indonesia; Islamic sects -- Indonesia